AUTOIGNITION TENDENCIES OF SOME TURKISH LIGNITES - (:unkn) unknown (BUTTERWORTH-HEINEMANN LTD, 1993)
The relative autoignition tendencies of five Turkish lignites were determined by an adaptation of the ACIRL crossing-point method. A relation was observed between the crossing point and the difference between the volatile matter and moisture contents of the five lignites, similar to that shown by Australian coals.
Keywords: LIGNITE; AUTOIGNITION; MOISTURE CONTENT; LOW-TEMPERATURE OXIDATION; VICTORIAN BROWN COAL; OXYGEN